Penentuan Suhu Reaksi Terbaik Pada Saponifikasi Stearin - Fatmayati, Fatmayati (Jurnal Sains dan Ilmu Terapan, 2018)
Crude palm oil fractionation produces one product that is stearin. In general the industry utilizing stearin as a raw material for making margarine. If the saponification process is carried out at stearin it will produce two products at once, namely soaps and glycerol. This research aims to determine the best reaction temperature to produce soap and glycerol by saponification stearin. Saponification using ethanol with KOH 3N reacting with palm stearin obtained as a byproduct of oil production in the mini plant Polytechnic Kampar. The reaction was performed with the reaction temperature variation of 60, 65, 70, 75 and 80 °C with stirring 400 rpm for 60 minutes. Results saponification separated to get the soap and glycerol are then analyzed to determine whether soap and glycerol produced is appropriate or not the relevant SNI. In all the saponification reaction temperature variations do, produce soap with characteristics in accordance with SNI 06-3532-1994.